Issues relating to regulatory enforcement in the communications sector in Malaysia / Liew Horng Bin - Liew, Horng Bin (2008)
This paper seeks to examine and present a review of the correlation between the institutional structure of the regulatory body, in this case the Malaysian Communications and Multimedia Commission (MCMC), and the exercise of its enforcement powers provided under the Communications and Multimedia Act 1998 ('CMA 1998'), in the face of the convergence of telecommunication, broadcasting and multimedia industries in Malaysia. The focus of this paper is to highlight the various enforcement mechanisms envisaged under the CMA 1998 and the corresponding effectiveness in view of the institutional setting therein. Central to the instant study is the possibility and viability of civil enforcement of the various provisions enumerated under the CMA 1998, apart from the conventional state-criminal prosecution on any potential infringements.